Comparative Assessment of Utilization and Hospital Outcomes of Veterans Receiving VA and Non‐VA Outpatient Dialysis. (9th August 2018) - Wang, Virginia; Coffman, Cynthia J.; Stechuchak, Karen M.; Berkowitz, Theodore S.Z.; Hebert, Paul L.; Edelman, David; O'Hare, Ann M.; Weidenbacher, Hollis J.; Maciejewski, Matthew L.
Abstract : Objective: Growing demand for VA dialysis exceeds its supply and travel distances prohibit many Veterans from receiving dialysis in a VA facility, leading to increased use of dialysis from non‐VA providers. This study compared utilization and hospitalization outcomes among Veterans receiving chronic dialysis in VA and non‐VA settings in 2008–2013. Data Sources: VA, Medicare, and national disease registry data. Study Design: National cohort of 27, 301 Veterans initiating dialysis, observed for a period of 2 years after treatment initiation. We used multinomial logistic regression to examine associations between patient characteristics and dialysis use in VA, non‐VA community settings via VA Purchased Care (VA‐PC), community settings via Medicare, or Dual settings. Zero‐inflated negative binomial regression was used to compare risk of hospitalization and days spent in the hospital across dialysis settings. Principal Findings: Sixty‐seven percent of Veterans obtained community‐based dialysis exclusively via Medicare, 11 percent in the community via VA‐PC, 4 percent in VA, and 18 percent in Dual settings. Financial and geographic access factors were important predictors of dialysis setting, but days spent in the hospital and risk of hospitalization did not differ meaningfully across settings. Conclusions: Most Veterans obtained dialysis in the community. Dialysis setting appeared to have little impact on risk of hospitalization among Veterans.